OPTIMIZATION OF AIRPORT PORTER SERVICE ON PASSENGER SERVICE SATISFACTION AT SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN INTERNATIONAL AIRPORT - Afkarina Malinda, Nadya; Hariyanto, Didi; Fatimah, Siti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airport Services are services provided to users of airport services by airport operators. The need for airport infrastructure to support airport service activities includes more systematic and proactive management of processes, procedures, facilities and equipment. In addition, the overall coordination involves multiple entities with multiple functional jurisdictions in real time. To answer this need, Angkasa Pura 1 provides Airport Porter Service personnel who are vendors (collaboration) to make it easier for passengers to transport baggage onto the plane. In PM 178 of 20015 there is a point that we must provide comfort facilities for passengers, one of these facilities is the ease of transporting baggage. This study aims to determine the design of Airport Porter Service facilities on Passenger Satisfaction with passenger baggage transportation services at Sultan Aji Muhammad Sulaiman Sepinggan International Airport, Balikpapan. This study uses a quantitative descriptive writing method. Using premier and secondary data sources, with data collection techniques namely observation, interviews and literature study which are then analyzed by simple regression analysis to determine the relationship or influence of the variables studied. The result showed that the implementation of Airport Porter Service at Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan International Airport, according to officers and passengers, has been going well, but they still need to pay attention to several things to improve porter services. The results of the study also show that Airport Porter Service has a significant effect on Passenger Satisfaction